Attitudes on gun violence and gun control - Quek, Cherine Ang Rui @ Rinaporn Katiya (2019)
Our study investigated how the degree of vicariously-acquired learned helplessness about gun violence in the United States would affect the perceptions of radical groups that supported gun control. For appropriateness to the gun violence context, we defined radical groups as group actions that are extreme and cause long-term disruption to others’ lives to achieve a goal. We hypothesised that individuals high on vicariously-acquired learned helplessness on gun violence would perceive radical groups as being more effective in achieving their goal. Consequently, these learned helpless individuals would identify more with members of the radical group. Thirty-six American citizens (23 males; Mage = 39.58; SDage = 11.32) were recruited from MTurk and completed the self-reported measures on Qualtrics. Hierarchical regression analyses did not support our hypotheses. Regardless of whether individuals were learned helpless or not about gun violence, there was no difference in perceptions of collective efficacy for both radical and non-radical groups (p = .46). Regardless of whether individuals were learned helpless or not about gun violence, there was no difference in group identification for both radical and non-radical groups (p = .23). However, additional analyses found partial support for our second hypotheses; when intentions to interact was used as an indirect measure for group identification, individuals who were low on vicariously-acquired learned helpless about gun violence had higher intentions to interact with a less radical group (p < .05). We discussed potential reasons for our non-significant findings, mainly relating to how radical groups were defined, which could be addressed in future studies.